Macrophages protect against loss of adipose tissue during cancer cachexia. Issue 5 (18th July 2019) - Erdem, Merve; Möckel, Diana; Jumpertz, Sandra; John, Cathleen; Fragoulis, Athanassios; Rudolph, Ines; Wulfmeier, Johanna; Springer, Jochen; Horn, Henrike; Koch, Marco; Lurje, Georg; Lammers, Twan; et al.
Abstract: Background: Cancer cachexia represents a central obstacle in medical oncology as it is associated with poor therapy response and reduced overall survival. Systemic inflammation is considered to be a key driver of cancer cachexia; however, clinical studies with anti‐inflammatory drugs failed to show distinct cachexia‐inhibiting effects. To address this contradiction, we investigated the functional importance of innate immune cells for hepatocellular carcinoma (HCC)‐associated cachexia. Methods: A transgenic HCC mouse model was intercrossed with mice harbouring a defect in myeloid cell‐mediated inflammation. Body composition of mice was analysed via nuclear magnetic resonance spectroscopy and microcomputed tomography. Quantitative PCR was used to determine adipose tissue browning and polarization of adipose tissue macrophages. The activation state of distinct areas of the hypothalamus was analysed via immunofluorescence. Multispectral immunofluorescence imaging and immunoblot were applied to characterize sympathetic neurons and macrophages in visceral adipose tissue. Quantification of pro‐inflammatory cytokines in mouse serum was performed with a multiplex immunoassay. Visceral adipose tissue of HCC patients was quantified via the L3 index of computed tomography scans obtained during routine clinical care. Results: We identified robust cachexia in the HCC mouse model as evidenced by a marked loss of visceral fat and lean mass. Computed tomography‐based analyses demonstrated that a subgroup of human HCC patients displays reduced visceral fat mass, complementing the murine data. While the myeloid cell‐mediated inflammation defect resulted in reduced expression of pro‐inflammatory cytokines in the serum of HCC‐bearing mice, this unexpectedly did not translate into diminished but rather enhanced cachexia‐associated fat loss. Defective myeloid cell‐mediated inflammation was associated with decreased macrophage abundance in visceral adipose tissue, suggesting a role for local macrophages in the regulation of cancer‐induced fat loss. Conclusions: Myeloid cell‐mediated inflammation displays a rather unexpected beneficial function in a murine HCC model. These results demonstrate that immune cells are capable of protecting the host against cancer‐induced tissue wasting, adding a further layer of complexity to the pathogenesis of cachexia and providing a potential explanation for the contradictory results of clinical studies with anti‐inflammatory drugs.